Allelic diversity of genes controlling responses to vernalization and photoperiod among spring bread wheat varieties of diverse geographic origin - Zh. T. Kalybekova (Труды по прикладной ботанике, генетике и селекции, 2020)
Spring bread wheat is the most important cereal crop, cultivated under various climatic conditions and on different latitudes. Modern molecular genetic studies of wheat are aimed at investigating the crop’s genetic potential. By now, molecular markers have been developed to identify alleles of the Vrn (vernalization response) and Ppd (photoperiod response) genes. Vrn genes are responsible for crop development rate regulation and crop yield structure. Ppd genes determine the response of plants to the length of the day, that is, the timing of flowering and the beginning of heading in plants under different cultivation conditions. The use of diagnostic DNA markers made it possible to analyze the presence of allelic combinations of the Vrn and Ppd genes in local and commercial wheat varieties from Europe, Asia, North and South Americas, Africa and Australia. This review summarizes the results of studies on the distribution of alleles of Vrn and Ppd genes in wheat breeding material over different geographical areas of its cultivation. For example, the dominant Vrn-A1a allele was found in 62% of European varieties; 52% of the studied Turkish wheat varieties carried dominant Vrn-B1 alleles. A dominant Vrn-D1 was found in 61% of Pakistani wheat accessions. Vrn-D1 is present in 41.9% of the studied varieties of Chinese wheat. Higher incidence of Ppd-D1A is typical for West European varieties. A Ppd-D1a allele was found in 58.6% of varieties preserved in the Turkish wheat collection, with a 60% frequency of this allele in commercial cultivars. Among local Afghan varieties, 97% are sensitive to photoperiod (carriers of Ppd-D1b); they are distributed throughout the country without much dependence on agroecological zones. All Pakistani varieties are insensitive to photoperiod (carriers of Ppd-D1a). In China, the highest incidence of the Ppd-D1a allele was observed in zone VII (87.5% of varieties).